Dampak Interaksi Sosial dalam Live Streaming Tiktok terhadap Kepercayaan Konsumen dan Keputusan Pembelian Pada Produk Skintific - nur kumala sari; Aisyah Megasari; Komarun Zaman (Jurnal Ekonomi Manajemen dan Bisnis, 2025)
This study aims to evaluate the influence of social interactions in TikTok live streaming on consumer trust and purchasing decisions for Skintific products. The study employed a quantitative approach. The study population was drawn from the average number of active viewers who followed live broadcasts on Skintific's official account during the week prior to the study. The sampling technique used was purposive sampling, with the sample size determined using the Slovin formula, resulting in 100 respondents. Data analysis was performed using a simple linear regression test. The results showed that social interactions in live streaming positively influenced consumer trust, positively impacted purchasing decisions, and significantly influenced both variables simultaneously.